1996
DOI: 10.1097/00000539-199610000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Primary Pulmonary Hypertension in Patients Undergoing Liver Transplantation

Abstract: Primary pulmonary hypertension (PPH) in patients with hepatic cirrhosis is often considered an unacceptable condition for liver transplantation because of increased morbidity and mortality during the procedure. We studied the incidence, characteristics, and final outcome of patients with PPH undergoing liver transplantation in our institution. Among the 226 patients undergoing 257 liver transplantations, eight (3.5%) fulfilled the conditions of PPH and responded to vasodilator therapy. Nitroglycerin 1.5 microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0
7

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
1
24
0
7
Order By: Relevance
“…Previous studies have shown that patients with mild PPHTN do not have increased mortality or require specific therapy (20–23). In contrast, cirrhotic patients with moderate‐to‐severe pulmonary hypertension have very high mortality (2,6,7,23).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with mild PPHTN do not have increased mortality or require specific therapy (20–23). In contrast, cirrhotic patients with moderate‐to‐severe pulmonary hypertension have very high mortality (2,6,7,23).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient demonstrated a significant and persisting decrease in PVR and PAP during an eight‐month period of long‐term epoprostenol therapy. PAP and PVR values in our patient immediately before skin incision were within the range which is well tolerated during OLT if PPH is not treated with epoprostenol (15–17). However, our patient developed perioperative right heart failure, eventually necessitating mechanical circulatory support.…”
Section: Discussionmentioning
confidence: 53%
“…OLT is well tolerated in patients with only mild or moderate PPH (15–17). Perioperative mortality rates in these patients are comparable to mortality rates in patients without PPH (15–17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations